Design Studies of Ultra-Wideband Microstrip Antennas with a Small Capacitive Feed - Veeresh G. Kasabegoudar; Dibyant S. Upadhyay; K. J. Vinoy (International Journal of Antennas and Propagation)
The design of an ultra-wideband microstrip patch antenna with a small coplanar capacitive feed strip is presented. The proposed rectangular patch antenna provides an impedance bandwidth of nearly 50%, and has stable radiation patterns for almost all frequencies in the operational band. Results presented here show that such wide bandwidths are also possible for triangular and semiellipse geometries with a similar feed arrangement. The proposed feed is a very small strip placed very close to the radiator on a substrate above the ground plane. Shape of the feed strip can also be different, so long as the area is not changed. Experimental results agree with the simulated results. Effects of key design parameters such as the air gap between the substrate and the ground plane, the distance between radiator patch and feed strip, and the dimensions of the feed strip on the input characteristics of the antenna have been investigated and discussed. As demonstrated here, the proposed antenna can be redesigned for any frequency in the L-, S-, C-, or X-band. A design criterion for the air gap has been empirically obtained to enable maximum antenna bandwidth for all these operational frequencies.